DIGITAL WHITEBOARD: MAPPING OF RESOURCES FOR USE IN THE CLASSROOM - Santos, Leila Maria Araújo; Varaschini, Patricia Luiz; Martins, Sandro Luiz Moresco (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper reports on the research being carried out with the financial support of the Center for Educational Technology and Coordination of UAB UFSM - Final Tender Protocol 17/2012, with the objective of map and document the Digital Whiteboard technological resources. This mapping would serves for the development of an educational material to support the teachers in the use of digital whiteboard teaching.